Diastolic properties of the normal left ventricle during supine exercise. Issue 1 (July 1988) - Nonogi, H; Hess, O M; Ritter, M; Krayenbuehl, H P
Abstract : Diastolic function in response to dynamic exercise was studied by biplane left ventriculography and by measuring left ventricular pressure with a high fidelity micromanometer tipped catheter at rest and during supine bicycle exercise in nine normal subjects. During exercise there was a fall in end systolic volume, in the time constant of left ventricular isovolumic pressure decay, and in the lowest diastolic pressure. Stroke volume, peak filling rate, mean passive filling rate, and the volume at the lowest diastolic pressure increased. There was an increase in the number of time constants that had elapsed before the lowest diastolic pressure was reached and the slope of the pressure-volume curves during passive filling (delta P/delta V) increased without changes in end diastolic pressure and volume. These results show that during exercise elastic recoil is enhanced and left ventricular relaxation is faster and more complete. Both phenomena reduce the lowest diastolic filling pressure. The observed increase in chamber stiffness from rest to exercise is probably related to increased resistance of the left ventricular wall caused by higher passive filling rates. The enhanced early diastolic pressure decay during exercise allows stroke volume to increase despite an increase in diastolic viscoelastic resistance and chamber stiffness.